Strengthening IMF Crisis Prevention - Ostry, Jonathan (IMF Working Papers; Working Paper ;, 2005)
To better fulfill its crisis-prevention mandate, IMF surveillance needs to provide stronger incentives for countries to follow good policies and for markets to avoid boom-bust cycles in capital flows. To this end, surveillance should culminate in a summary public assessment of the quality of a country's policies and stipulate the actions needed to address shortcomings. A country's potential access to IMF credits should be linked to the quality of its policies in noncrisis periods in order to create stronger incentives for better policies and reduce incentives for capital to flow where it cannot be used in socially beneficial ways.